The Influence Of Organizational Commitment To Academic Achievement Of BEM UHAMKA Students - Pahman Habibi; Fitrisia Fitrisia (Universitas Muhammadiyah Prof. DR HAMKA., 2020)
This study aims to examine the effect of organizational commitment either partially or simultaneously on BEM UHAMKA students' academic achievement. The independent variable is an organizational commitment consisting of 3 dimensions: affective dedication, continuance commitment, and normative commitment. Simultaneously, the dependent variable is student academic achievement, measured by the student's I.P. last semester. The research sample was 43 BEM UHAMKA students. Data collection techniques using a questionnaire and data analysis used is multiple linear regression. The results obtained are Organizational commitment in terms of the dimensions of useful dedication, continuance commitment, and normative commitment simultaneously have a significant positive effect on academic achievement.